The Impact of Surgical Site Infection to the Health Care Cost - Triani Marwati; A.A. Subiyanto; Totok Mardikanto; Priyambodo Priyambodo; Marsiana Wibowo; Nurul Qomariyah (International Journal of Public Health Science (IJPHS), 2016)
Surgical Site Infection (SSI) is the most common cause of nosocomial infections. The incidence of SSI is ranging between 14 - 16% of the entire incident of nosocomial infections in hospitalized patients. The objectives of this study were to determine the relationship between knowledge, attitude, infrastructure and behavior of health personnel to prevent SSI and to determine the amount of additional costs for hospital care as a result of SSI. This study used a mixed method research. Quantitative research conducted with descriptive analytic design with cross sectional approach. Quantitative data was analyzed by univariate and bivariate analysis. Qualitative research was used to measure additional cost due to SSI. Health personnel showed good knowledge about SSI prevention (89.6%), good attitude towards SSI prevention (57%), assessed good for hospital infrastructure (93.8%), but only 55.2% showed good behavior to prevent SSI. There were no relationship between knowledge and attitudes of health personnel, and hospital infrastructure with health personnel behavior to prevent SSI. Additional cost due to SSI was IDR 18,375,000 for each patient.